Nurture through nature: a comparative study between standard and nature-based play in outdoor preschool environments - Fiala, Abigail L. (Kansas State University, 2017)
Nature-based play is gaining attention in early childhood education because of the social, physical, and cognitive benefits from interacting with nature at a young age (International Play Association 2014). Some studies provide strong evidence to suggest that nature-based unstructured play can have a positive benefit on early childhood development and improve the socialization, problem solving, confidence, creativity, autonomy, and self-awareness in children as well as their physical health (Fjortoft 2004, Louv 2005). The purpose of this study is to identify differences in play behavior among preschoolers that may influence early childhood development between standard or traditional playgrounds and playgrounds designed with interaction with nature, or access to nature, and, thus, to suggest design solutions for play environment, which responds to the issues this research identifies. This is a comparative observational study on play behavior between two study settings, including nature-based and standard/traditional-play environments with nature-access . Comparative observations were conducted at the Center for Child Development (nature-based) and Hoeflin Stone House Early Childhood Center (standard) at Kansas State University in Manhattan, Kansas. Preschoolers’ play behaviors and behavior-environment interactions in both settings were compared using behavioral mapping and time-lapse observation (20 minutes per subject) techniques in which their location, activities, and interactions were recorded. Findings suggest that children in nature-based playgrounds are more likely to be physically active and creative with their play. Also, movable and manipulative play elements (“loose parts”) allow children to engage in more social activities than standard anchored playground element vs. standard playgrounds, however, allow children to explore games with rules and provide valuable development for motor and social skills. Therefore, this study suggests a design approach that is a hybrid between designed nature and standard play in a way that utilizes the positive aspects of both types of play. These findings will lead to a call for research and design into the direction of creating outdoor play environments that infuse standard play structures with natural environments.
Keywords: Landscape architecture; Early childhood development; Nature play; Playground design